Health impact assessment by ingestion of polluted soil/sediment (Rudarsko-geološko-naftni zbornik, 2016)
Potentially toxic elements (PTEs) pose a threat to human health as they can easily enter human body via ingestion of polluted soil/sediment. In order to estimate bioavailability and access health impact on people, measurement of the oral bioaccessibility of a contaminant is crucial. Various laboratory based in vitro tests which mimic human gastrointestinal tract conditions can be used. In order to set up the method for analysing bioaccessibility of contaminants in soil samples in Laboratory for the analysis of geological materials at Department of Mineralogy, Petrology and Mineral resources (Faculty of Mining, Geology and Petroleum Engineering, University of Zagreb - RGNF), with regards to the available equipment, an orientation survey was carried out in collaboration with the Department of Biochemical Engineering (Faculty of Food Technology and Biotechnology, University of Zagreb - PBF). The digestion of two different samples in synthetic fluids (gastric and intestinal fluid) was performed simultaneously at RGNF laboratory and PBF laboratory under different extraction conditions according to each laboratory’s ability. Prior to analysis of bioaccessibility, detailed mineralogical and chemical characterization of samples was performed. The comparison of two experiments showed that there is a relatively good correlation between concentrations obtained after digestion of samples in different labs, under different conditions. As a result of this study, an efficient and relatively inexpensive method for determining the bioaccessibility was set up at Faculty of Mining, Geology and Petroleum Engineering, which makes this kind of tests more accessible and enables new approach in risk assessment studies.